Business in networks : - HÅKANSSONx, H.; FORD, D.; GADDE, L.; SNEHOTA, I.; WALUSZEWSKI, A. (John Wiley & Sons Ltd, 2009)
This book provides an overview of the process of business interaction and an explanation of how companies work with each other interactively in business networks. It draws conclusions about the way that business evolves and develops and about how companies can operate effectively in an interactive world